2019
DOI: 10.1111/iwj.13207
|View full text |Cite
|
Sign up to set email alerts
|

The effects of platelet‐rich‐plasma gel application to the colonic anastomosis in hyperthermic intraperitoneal chemotherapy: An experimental rat model

Abstract: Hyperthermic intraperitoneal chemotherapy (HIPEC) has cytotoxic effects on tumour cells but also negative impacts on anastomotic healing. Platelet‐rich‐plasma (PRP) is used for wound care but data about effects on gastrointestinal anastomosis are limited. In this experimental study, we aimed to investigate the effects of PRP application on colon anastomosis in rats those received HIPEC with cisplatin. Five rats were sacrificed to obtain PRP gel. Thirty rats were divided into three groups; Group 1: control grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…These results show that the HIPEC procedure decreases tissue hydroxyproline levels in colon anastomosis, but this situation can be improved by the PRP gel application that increases these levels. In our study, significantly lower tissue hydroxyproline levels were detected in the 5‐FU HIPEC groups, which is consistent with the literature 10,24 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results show that the HIPEC procedure decreases tissue hydroxyproline levels in colon anastomosis, but this situation can be improved by the PRP gel application that increases these levels. In our study, significantly lower tissue hydroxyproline levels were detected in the 5‐FU HIPEC groups, which is consistent with the literature 10,24 …”
Section: Discussionsupporting
confidence: 93%
“…There was also a statistically significant difference between the 5‐FU group and the 5‐FU + PRP group ( P = 0.047), which indicates that PRP significantly increases ABP. These findings suggest that the negative effect of HIPEC on anastomotic healing can be reversed by the application of PRP gel, which is supported by similar studies in the literature 13,23,24,27 …”
Section: Discussionsupporting
confidence: 81%
“…Association of topical PRP application to anastomosis line with better wound healing has also been reported in other studies of rat colon anastomosis models, based on increased ABP values and higher tissue hydroxyproline levels accompanied with histopathological findings of decreased inflammatory cell infiltration, marked fibroblast development, and rich collagen production identified in the PRP vs. the control group of rats [12,14]. Similarly, Ocak et al reported that PRP administration to intestinal anastomosis in rats that underwent hyperthermic intraperitoneal chemotherapy (HIPEC) decreased inflammatory response, increased anastomotic bursting pressure, and increased hydroxyproline levels [24].…”
Section: Gastroenterology Research and Practicesupporting
confidence: 54%
“…Depending on the origin of the used cancer cells, rat and mouse strains were chosen. The following rat types were used in the analyzed articles; Wistar (21%) [ 32 , 45 , 46 , 62 , 63 , 64 ], Sprague Dawley (32%) [ 40 , 43 , 51 , 52 , 57 , 65 , 66 , 67 , 68 ], WAG/Rij (32%) [ 47 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] and athymic/nude (14%) [ 44 , 76 , 77 , 78 ] rats. For mouse experiments, the following strains were used: Swiss albino (20%) [ 36 , 38 , 79 ], athymic (33%) [ 37 , 48 , 50 , 55 , 80 ], C57BL/6 (20%) [ 33 , 39 , 81 ], BALB/c (20%) [ 49 , 56 , 82 ] and NOD-SCID (7%) [ 34 ].…”
Section: Preclinical Hipec Modelsmentioning
confidence: 99%